Leadership in Malaysian paddy farming - Masso, Wisam Yako Aziz; Man, Norsida (Faculty of Computer Science and Information Technology, Universiti Putra Malaysia, 2015)
Agriculture has a vital role in our livelihood and economic development unlike any other economic activity. Malaysia's leading agricultural yields are in rice, fruit and vegetables. The growing of rice takes up the biggest area, comprising 670,000 ha in 2010 (Dorward, Poole et al. 2003). There are 0.3 million paddy farmers in Malaysia, 40% of which are full-time, and 65% of total paddy farms are below one hectare in area (Alam, Siwar et al. 2010). In nascent economies like Malaysia, rural people have relied on extension workers for technical advice and knowledge. The success of extension programs is decided to a great extent by the ability of extension workers, their qualifications and competency, since the whole extension process is reliant on their passing of new ideas and technical advice to the rural people (Idris, Hamzah et al. 2010). In the area of agricultural extension, leadership has crucial longterm importance as it deals with educating groups of farmers in the community (Khalil 2008). Local leaders are able, in an informal manner, to shape the behavior and attitudes of others towards what is desirable, and the leadership in rural areas has a paramount function in the agricultural extension program (Rogers.2010).